2018
DOI: 10.1021/acs.iecr.8b02742
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Strained Bimetallic PtFe Nanocatalysts Show Tunable Catalytic Selectivity in Aqueous Oxidation of Bio-Polyols to Dicarboxylic Acids

Abstract: Rational control of catalytic selectivity still remains a grand challenge in the field of biomass conversion to valueadded chemicals. In this paper, we used PtFe catalyst as an example to understand fundamentals for lattice strain, electronic reconfiguration, reaction kinetics and catalytic selectivity for aqueous conversion biopolyols. Structurally strained face centered tetragonal (fct) PtFe crystals were synthesized and it was confirmed that such unique PtFe nanostructures display intriguing electronic coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The procedure has been discussed previously, and it is thus stated briefly. Pt(111) surfaces were modeled using a triple-layer p (4 × 4) slab comprising three metal layers with 16 atoms per layer, and each slab was separated by a vacuum of 17 Å to ensure that the interaction between neighboring cells was negligible, which is similar to our previously reported method. , All DFT calculations were performed using the CASTEP code. , Using the PBE functional, the exchange-correlation effects were described with the generalized gradient approximation (GGA). The electron wave functional was expanded by a plane-wave basis set with a cutoff energy of 400 eV.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The procedure has been discussed previously, and it is thus stated briefly. Pt(111) surfaces were modeled using a triple-layer p (4 × 4) slab comprising three metal layers with 16 atoms per layer, and each slab was separated by a vacuum of 17 Å to ensure that the interaction between neighboring cells was negligible, which is similar to our previously reported method. , All DFT calculations were performed using the CASTEP code. , Using the PBE functional, the exchange-correlation effects were described with the generalized gradient approximation (GGA). The electron wave functional was expanded by a plane-wave basis set with a cutoff energy of 400 eV.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Pt­(111) surfaces were modeled using a triple-layer p (4 × 4) slab comprising three metal layers with 16 atoms per layer, and each slab was separated by a vacuum of 17 Å to guarantee the interaction between neighboring cells was negligible, which is similar to our previously reported method. , All DFT calculations were performed using the CASTEP code. , The exchange-correlation effects were described with the generalized gradient approximation (GGA) using the PBE functional. The electron wave functional was expanded by a plane-wave basis set with a cutoff energy of 400 eV.…”
Section: Methodsmentioning
confidence: 99%
“…15 Polyol reduction method (EG, 3.5 ± 0.1 nm): A polyol reduction process was applied to prepare the bimetallic PtPd/C catalysts as reported. 62 In-situ reduction method (NaBH 4 , 3.9 ± 0.4 nm): In a typical catalyst synthesis process, as reported previously, 63 the preparations of monometallic Pt/C, Pd/C, and bimetallic PtPd/C catalysts were conducted following a one-pot wet chemistry approach using NaBH 4 . Impregnation method (I.W.I., 5 TEM and high-resolution transmission electron microscopy (HRTEM) images were obtained on a JEOL JSM-2010.…”
Section: ■ Introductionmentioning
confidence: 99%
“…120 The results of high current density, excellent durability, and good CO poisoning tolerance made the addition of Fe into noble metal alloy a suitable potential for alcohol electrooxidation. 121 Jin et al 122,123 reported on the observation of interdiffused fct Pt-Fe nanocrystals that exhibited threefold higher activity than fcc Pt-Fe catalysts. Fe near Pt atoms in fct structure believed to decrease the binding energy between Pt surface and C O groups, which assisted surface to molecules oxygen transfer.…”
Section: Development Of Pt-based and Pd-based Catalyst With Iron Metalmentioning
confidence: 99%